Further Thoughts on Aspects of Emily Brontë's poems. (3rd April 2017) - Chitham, Edward
Abstract : There is much work to be done on our understanding of the role played in the lives of Emily and Anne Brontë by their fictional land of Gondal. Here I propose to deal with three issues: (a) What more can we say about 'Gondal's Queen'? (b) When did Gondal end? (c) Is there anything further to say about the poem 'Often Rebuked'? These are contributions to discussion, certainly not final. Both Emily and Anne separated their work in their manuscripts into Gondal and non-Gondal poems. Emily's copy manuscripts are usually known as A (non-Gondal) and B (Gondal).